2011
DOI: 10.1002/cphc.201100079
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Compositional Characterization of Self‐Preserved Gas Hydrates by Low‐Vacuum Scanning Electron Microscopy

Abstract: Unequal interactions: A backscattering electron microscopy study reveals that some Kr hydrates can be trapped in ice products during dissociation (see image) whereas no clear evidence of such a phenomenon is found for Ar samples. Also, the texture of ice from Ar‐hydrate decomposition is more cohesive than that observed for Kr samples. The different dissociation behavior between the two systems may be attributed to differences in the interaction between gas and water molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(55 reference statements)
2
11
0
Order By: Relevance
“…The term "self-preservation" of gas hydrates was coined in Russia after researchers discovered that gas hydrate dissociation stopped soon after the onset of experiments when hydrate particles became coated with ice films. Later on, the results were corroborated and extended with data from more thorough experiments on structural changes in hydrates of methane and other gases capable of self-preservation [22][23][24][32][33][34][35][36][37][38][39][40][41][42]. The results were the basis for a unique technology of using hydrates as a gas storage and transportation media due to their very slow dissociation at <0 • C and 0.1 MPa [43][44][45][46].…”
Section: Introductionmentioning
confidence: 65%
“…The term "self-preservation" of gas hydrates was coined in Russia after researchers discovered that gas hydrate dissociation stopped soon after the onset of experiments when hydrate particles became coated with ice films. Later on, the results were corroborated and extended with data from more thorough experiments on structural changes in hydrates of methane and other gases capable of self-preservation [22][23][24][32][33][34][35][36][37][38][39][40][41][42]. The results were the basis for a unique technology of using hydrates as a gas storage and transportation media due to their very slow dissociation at <0 • C and 0.1 MPa [43][44][45][46].…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have shown that dissociation of metastable hydrate in the range 270 K < T < 273 K yields metastable supercooled water, , which converts into ice; therefore, ice formation during reformation could not be ruled out. It may also be possible that some of the reformed hydrates were also trapped inside ice sheet during the reformation. , Metastable hydrates are fundamentally identical to hydrates, and direct conversion of hydrate into ice was not feasible due to the high energy barrier to nucleate hexagonal ice from hydrates . Reformation was initiated due to disturbance caused by hydrate melting or gas and water migration that triggered the sudden onset of solidification due to the cavitation phenomenon .…”
Section: Resultsmentioning
confidence: 99%
“…It may also be possible that some of the reformed hydrates were also trapped inside ice sheet during the reformation. 79,26 Metastable hydrates are fundamentally identical to hydrates, and direct conversion of hydrate into ice was not feasible due to the high energy barrier to nucleate hexagonal ice from hydrates. 75 Reformation was initiated due to disturbance caused by hydrate melting or gas and water migration that triggered the sudden onset of solidification due to the cavitation phenomenon.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…According to the data of ref , 0.5 mm particles of natural gas hydrate were preserved for 2 weeks. As it has been shown recently, an ice shell around a decomposing hydrate particle does not form in all cases. , During the decomposition of argon hydrate, the formed ice is released as a crust, but in the case of krypton hydrate, a mixture of hydrate microparticles and ice is formed.…”
Section: Introductionmentioning
confidence: 95%
“…As it has been shown recently, an ice shell around a decomposing hydrate particle does not form in all cases. 37,38 During the decomposition of argon hydrate, the formed ice is released as a crust, but in the case of krypton hydrate, a mixture of hydrate microparticles and ice is formed. Many studies of the influence of external factors on the selfpreservation of hydrates are presented in the literature.…”
Section: Introductionmentioning
confidence: 99%